Chinese prodigal : a memoir in eight arguments - Shih, David, 1970- (Atlantic Monthly Press, 2023)
"From an exciting and sharp-voiced new observer of American culture, a forthright and probing debut exploring Asian American identity in a racially codified country. After his father's passing in 2019, David Shih sought to unravel the underlying tensions that defined the complex relationship between him and his parents--a question that ultimately forced a reckoning with the expectations he encountered as the only son of Chinese immigrants and the realities of what it means to be Asian in a segregated country. Chinese Prodigal is a candid examination of a society and the people it has never made space for. In public life and in Shih's own, "Asian Americanness" has changed shape constantly, directed by the needs of the country's racial imaginary. A sliding scale, visibility for Asians in America has always been relative, something that only comes into focus when it aligns with broader political agendas. Structured as a memoir in essays, Chinese Prodigal examines the emergence of "Asian American" in a post-Civil Rights America, from the moment the concept took political hold with the construction of the model minority myth, then galvanizing in the wake of the death of Vincent Chin in 1980s Detroit, and on through the vexed place of Asians and Asian Americans in the right-wing effort to dismantle affirmative action and remake public education. Present in the food we eat, the jobs we take, and the ways we parent, the process of becoming an American is defined by who and what you must sacrifice to survive and excel. A work of rare subtlety, Chinese Prodigal offers a new vocabulary for understanding a racial hierarchy too often conceptualized as binary. It is a moving testimony of a son, father, and citizen stepping outside the expectations imposed on him"--